2-tert-Butyl-1, 4-benzoquinone, a food additive oxidant, reduces virulence factors of Chromobacterium violaceum. (15th June 2022) - Xu, Kai-Zhong; Tan, Xiao-Juan; Chang, Zeng-Yan; Li, Jun-Jian; Jia, Ai-Qun
Abstract: Multi-drug resistant bacteria have been paying increasing attentions. Quorum sensing (QS) and QS-associated biofilms are showing the vital reasons for antibiotics resistant. In this study, 2- tert -butyl-1, 4-benzoquinone (TBQ), the oxidant of tert -butyl hydroquinone (TBHQ), can potentially be the QS inhibitor (QSI) of Chromobacterium violaceum ATCC12472. After treated with 50 μg/mL of TBQ, the violacein synthesis, chitinase, hemolysin and swimming motility of C. violaceum decreased by 70.6, 72, 70.5, and 88.45%, respectively. Further investigation demonstrated that combined TBQ (50 μg/mL) and ciprofloxacin (sub-MIC, 0.2 μg/mL) treatment not only inhibited biofilm formation by 73.27% but also improved the susceptibility of the biofilm to ciprofloxacin. The underlying mechanisms involved in the reduction of virulence factors and inhibition of biofilm formation were explored by quantitative real-time PCR, and confocal laser scanning microscopy (CLSM). The results showed that the expression levels of cvi I, cvi R, vio A, hsm P, chi A, and lol A were reduced by 51, 66, 49, 72, 77, and 72%, respectively. In addition, we determined that TBQ treatment could improve the survival rate of animal model Caenorhabditis elegans to 55.6% following infection with C. violaceum. Thus, food additive oxidant TBQ exhibits new QSI activity against C. violaceum and potential anti-biofilm application in food industry. Highlights: 2- tert -Butyl-1, 4-benzoquinone was first reported as a new quorum sensing inhibitor. 2- tert -Butyl-1, 4-benzoquinone reduces virulence of Chromobacterium violaceum. 2- tert -Butyl-1, 4-benzoquinone recovers the ciprofloxacin susceptibility of biofilm. 2- tert -Butyl-1, 4-benzoquinone reduces the toxicity of C. violaceum to Caenorhabditis elegans. 2- tert -Butyl-1, 4-benzoquinone can potentially resist biofilms in the food industry.